2006
DOI: 10.2220/biomedres.27.1
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating effect of vitamin D3 derivatives on type-1 cellular immunity

Abstract: ABSTRACT1α,25-dihydroxyvitamin D3 [Calcitriol or 1,25(OH) 2 D 3 ] is an important active metabolite involved in multiple functions but its calcemic effect in vivo limits its therapeutic applications. On the other hand, 22-oxa-1α,25-dihydroxyvitamin D 3 (22-oxacalcitriol or 22-Oxa-1α,25-D 3 ), a low calcemic analog of vitamin D3 (VitD3), has been widely used as a drug for the secondary hyperparathyroidism. Here, we investigated immunomodulating effect of these two VitD3 derivatives on the differentiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 37 publications
2
38
3
3
Order By: Relevance
“…We have shown that 1,25(OH) 2 D 3 has a distinct propensity to skew host response to C. albicans away from a ''proinflammatory'' profile through attenuation of TNF-a, IL-6, IFN-c as well as production of IL-17. Other researchers have reported inhibition of Th1 cytokine production with 1,25(OH) 2 D 3 , although not in the setting of Candida infection and polarization toward a Th2-type response [21][22][23]. In our system using human PBMC stimulated by C. albicans, we also observed an increase in IL-10 production in vitamin D presence.…”
Section: Discussionsupporting
confidence: 44%
“…We have shown that 1,25(OH) 2 D 3 has a distinct propensity to skew host response to C. albicans away from a ''proinflammatory'' profile through attenuation of TNF-a, IL-6, IFN-c as well as production of IL-17. Other researchers have reported inhibition of Th1 cytokine production with 1,25(OH) 2 D 3 , although not in the setting of Candida infection and polarization toward a Th2-type response [21][22][23]. In our system using human PBMC stimulated by C. albicans, we also observed an increase in IL-10 production in vitamin D presence.…”
Section: Discussionsupporting
confidence: 44%
“…Its effects include promotion of phagocytosis, superoxide synthesis and bacterial killing, but it is also reported to inhibit T-cell proliferation and production of Th1-type cytokines (74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84) and of antibodies by B-cells (85) , highlighting the paradoxical nature of its effects. Effects on Th2-type responses are not clear (86)(87)(88) and there may be an increase in numbers of regulatory T-cells (89,90) . Overall, the current evidence suggests that vitamin D is a regulator of immune function but that its effects will depend upon the immunological situation (e.g.…”
Section: Vitamin Dmentioning
confidence: 99%
“…With regard to conventional T cells, it has been shown that 1,25(OH) 2 D 3 and its analogues have the capacity to inhibit T-cell proliferation [32][33][34] and to modulate cytokine production 35,36 when activated with mitogens. Secretion of interferon-c and IL-17 was inhibited, 23 and IL-4 and IL-10 production was enhanced 23,[37][38][39] thereby favouring a bias towards Th2 differentiation.…”
Section: Human Regulatory T Cells Express Vdrsmentioning
confidence: 99%